Study Habit, Use of Library Resources and Students’ Achievement in English Language in Katsina State, Nigeria - Olatoye, Olufunke Omotoke; Yakubu, Hajara (NIU Journal of Social Sciences; Vol 5 No 3 (2019): KIU Journal of Social Sciences, Vol. 5 No. 3, September 2019, 2019)
This study investigated how study habit and use of library resources influence students’ achievement in English language in Katsina State. Three hundred and thirty three randomly selected students participated in the study. Three instruments were used to collect data for this study. They are: Study Habit Questionnaire, Use of Library Resources Questionnaire and English Language Achievement Test. The two independent variables (use of library resources and study habit) account for 0.7% of the total variance in students’ achievement in English Language (R 2 = 0.007, P> 0.05). The influence of the two variables put together is not significant. However, there is a significant positive relationship between study habit and use of library resources (r = + 0.632, P< 0.05). This implies that, the higher the level of study habit, the higher the use of library resources. Likewise, the lower the level of study habit, the lower the use of library resources. There is no significant difference between male and female students’ in use of library resources, study habit and English Achievement (t = - 1.431, -.370 and 1.146 respectively, P> 0.05).  The following recommendations were made: The school counsellors should ensure that students are trained in the art of study habit skills. Also, resources that are relevant to the academic needs of the students should be provided to attract students to use library. Keywords: English language achievement, gender, library resources, students, study habit